Digital revolution and artificial intelligence as challenges for today - Marsili, M.; Wróblewska-Jachna, J. (Media i Społeczeństwo, 2024)
This article addresses the social impact of the ongoing digital revolution through a critical analysis of the literature on the subject. The aim is to understand the dynamics of change, which is key to dealing with the complexities of the digital age and realising its potential for sustainable development. The information revolution and artificial intelligence pose significant challenges to modern society by marking a profound transformation through self-organising social changes that disrupt existing norms. The digital age has revolutionized information systems, much like Gutenberg's invention of movable-type printing press. While it enables scientific and economic progress, the information revolution raises ethical, moral and legal concerns. Social media have become ”weapons” in a hybrid conflict, where the intangible battleground is human cognitive systems.